Analysis of Treatment of 3 Patients with Acute-on-Chronic Liver Failure - Jun Lei; Yi-lan Zeng; Lv-ye Xu; Ying Wang (Case Reports in Medicine)
Acute-on-chronic liver failure (ACLF) is an acute liver decompensation that occurs within 4 weeks on the basis of chronic liver disease. At present, the treatments of ACLF include general supportive treatment, etiological treatment, prevention and treatment of complications, artificial liver treatment, and liver transplantation. Many studies suggest that stem cell therapy may become a new treatment for patients with ACLF. Our department has also tried the application of this treatment. Now, there are three cases of stem cell therapy for patients with ACLF by our department which will be briefly reported.